Visualization and Data Analysis 2012 2012
DOI: 10.1117/12.907486
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the perceptual salience of relationships in parallel coordinate plots

Abstract: We present three extensions to parallel coordinates that increase the perceptual salience of relationships between axes in multivariate data sets: (1) luminance modulation maintains the ability to preattentively detect patterns in the presence of overplotting, (2) adding a one-vs.-all variable display highlights relationships between one variable and all others, and (3) adding a scatter plot within the parallel-coordinates display preattentively highlights clusters and spatial layouts without strongly interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We’ve showed that adjusting line luminance on the basis of one of the scalar variables in parallel coordinates indicates trends between that variable and others (see Figure 5). 1 This technique might also effectively indicate groupings in other visualizations. However, when nearby elements all have a similar luminance, distinguishing neighbors again becomes challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We’ve showed that adjusting line luminance on the basis of one of the scalar variables in parallel coordinates indicates trends between that variable and others (see Figure 5). 1 This technique might also effectively indicate groupings in other visualizations. However, when nearby elements all have a similar luminance, distinguishing neighbors again becomes challenging.…”
Section: Discussionmentioning
confidence: 99%
“…1 This reveals the correlations between the first axis and each remaining axis. However, it doesn’t consistently separate local clusters of lines (see the upper halves of T_sonic and soil_H20).…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Another increasingly common technique for visualizing the relationships between variables in multidimensional data sets is parallel coordinates. Here, vertical axes corresponding to each variable scaled to a common height are placed next to each other and connected with lines representing different samples [ 25 ]. This technique has been enhanced by tools such as scatter plot matrix overlay [ 26 ], proximity-based shading [ 27 ] and clustering methods that eliminate overplotting [ 28 ].…”
Section: Introductionmentioning
confidence: 99%